Melatonin suppresses lung cancer metastasis by inhibition of epithelial–mesenchymal transition through targeting to Twist. (15th March 2019) - Chao, Chia-Chia; Chen, Po-Chun; Chiou, Pei-Chen; Hsu, Chin-Jung; Liu, Po-I; Yang, Yi-Chen; Reiter, Russel J.; Yang, Shun-Fa; Tang, Chih-Hsin
Abstract : The epithelial–mesenchymal transition (EMT) phenotype, whereby mature epithelial cells undergo phenotype transition and differentiate into motile, invasive cells, has been indicated in tumor metastasis. The melatonin hormone secreted by the pineal gland has an antioxidant effect and protects cells against carcinogenic substances that reduce tumor progression. However, the effects of melatonin in EMT and lung cancer metastasis are largely unknown. We found that melatonin down-regulated EMT by inhibiting Twist/Twist1 (twist family bHLH transcription factor 1) expression. This effect was mediated by MT1 receptor, PLC, p38/ERK and β-catenin signaling cascades. Twist expression was positively correlated with tumor stage and negatively correlated with MT1 expression in lung cancer specimens. Furthermore, melatonin inhibited EMT marker expression and lung cancer metastasis to liver in vivo . Finally, melatonin shows promise in the treatment of lung cancer metastasis and deserves further study.